Identification of a tyrosine-phosphorylated 35 kDa carboxy-terminal fragment (p35CagA) of the Helicobacter pylori CagA protein in phagocytic cells: processing or breakage? - Moese, Stefan; Selbach, Matthias; Zimny-Arndt, Ursula; Jungblut, Peter R.; Meyer, Thomas F.; Backert, Steffen (Proteomics, 2001)
Helicobacter pylori is a very common bacterial pathogen that causes gastric disease by inducing the infiltration of immune cells as an initial event. Virulent H. pylori strains express a type IV secretion system composed of several virulence (Vir) proteins encoded by the cag pathogenicity island (cag PAI). During infection of phagocytic cells (U937, Josk-M and J774A.1) we have detected a de novo tyrosine-phosphorylated protein (p35p-Tyr) with sizes of 30 kDa, 38 kDa or 40 kDa, depending on the H. pylori strain. p35p-Tyr occurrence required functional virB4, virB7, virB10, virB11, virD4 and cagA (cytotoxin-associated gene A) genes encoded by the cag PAI suggesting that p35p-Tyr is a bacterial protein of variable size. We have biochemically purified p35p-Tyr from infected U937 cells. Tryptic peptides of p35p-Tyr determined by matrix-assisted laser desorption/ionization-mass spectrometry (MALDI-MS) identified the carboxy (C)-terminal part of the H. pylori CagA protein. Subsequent analysis by two-dimensional electrophoresis (2-DE) and immunoblotting using anti-CagA antibodies revealed the presence of three stable CagA protein species in phagocytes: (i) 130-140 kDa full-length CagA (p135CagA), (ii) a 100-105 kDa fragment (p100CagA) and (iii) a 30-40 kDa fragment (p35CagA). Unlike p135CagA, p35CagA and p100CagA were also detected in much lower amounts in H. pylori without host cell contact. Therefore, breakage or processing leads to the production of p35CagA and p100CagA, a process that is enhanced after translocation into host cells. MALDI-MS data and the isoelectric point determined by both 2-DE and sequence analysis suggested that p35CagA represents the C-terminal part of CagA and p100CagA corresponds to the remaining amino (N)-terminal fragment. The possible function of CagA in host signal transduction and development of gastric disease is discussed.